(untitled) (World Bulletin of Social Sciences, 2024)
Nowadays, technology in modern society is developing rapidly, especially artificial intelligence is becoming an integral part of our daily lives. This opens up new perspectives for both teachers and students in the field of education. This article is devoted to the effective use of artificial intelligence and its correct application in the field of education.